Teaching Strategies to develop Speaking skills concerning Contextual Factors a Comparison between Urban and Rural School Teachers from Imbabura - Espinoza Calderón, Dany Maribel (2021)
Identify how contextual factors such as the urban or rural character of the schools relate to foreign language teaching strategies to develop speaking skills.